The Twofoldedness of the Nature of Economic System - Lydeka, Zigmas (Ekonomika, 1999)
The internal mechanism of the existence of an economic system that ensures the interaction of economic phenomena is twofolded by its nature. The existence of a system can be expressed by the abundance of limit twofoldednesses: objectivity - subjectivity; naturalness - artificiality; self-organisation - organisation; accidentality - regularity; chaos - order; appearance - disappearance; complexity - simplicity; closedness - openness; statics - dynamics; stability - variability; freedom - compulsion; influence from personalities - influence from political groups; etc.The twofoldedness of existence of an economic system has an objective and subjective foundation: on the one hand, the existence is determined by regularities of functioning of the major complex systems; on the other hand, their dynamics is affected by the subjective factor, its diverse forms of manifestation, including the intellect that can foresee the variants of system development and turn it the direction wanted. People can recognise processes and influence them. People can create new life styles and alternative behaviour.I would assume that some kinds of twofoldedness of existence of an economic system should be considered initial ones transferring essential natural features into others. The comprehension of the natural twofoldedness is an important step in modelling derivative, transitional periods. To natural twofoldedness could be ascribed naturalness - artificiality, and self-organisation - organisation.The economic system is noted by way of self-organisation on the whole. The self-organisation of an economic system is a universal and general principle for its emergence and existence that does not depend on time and place (in place and time, certainly, only the form and range, the acknowledgement and negation, the limitation and encouragement of self-organisation may differ).A concrete economic system is noted for its exact way of external organisation, i.e., a concrete economic system has its own specifics. The organisation of the economic system depends on time and place, on goals of subjects participating in it and on their competence. In other words, different economic systems are noted for different ways of conscious organisation. Organisation could be regarded as a quality consciously ascribed to the economic system and improvement of the universal from of movement of the matter. If we want to understand the peculiarities of one or another economic system, we have to establish its structure and special ways of organisation.With regard to origin, functioning and possible transformation of the economic system, the following organisational forms of its existence should be specified: a) economic self-organisation that describes economics as a spontaneously developing, self-renewing. continuous phenomenon; b) economic organisation that introduces economics as an externally developed artificial phenomenon; c) economic disorganisation that expresses partial or whole destruction of organisation of the system and describes economics as an externally improved and modified artificial phenomenon; d) economic reorganisation that involves partial or whole construction of organisation of the system and describes economics as an externally renewed artificial phenomenon.